Cycle control with an extended-regimen oral contraceptive combining levonorgestrel and ethinyl estradiol that includes continuous low-dose ethinyl estradiol instead of the traditional hormone-free interval - Nappi, Rossella E (Int J Womens Health, 2017)
PURPOSE: To evaluate scheduled and unscheduled bleeding and spotting over 1 year of treatment with 91-day extended-regimen combined oral contraception (COC) providing continuous low-dose ethinyl estradiol (EE) in place of the traditional 7-day hormone-free interval (HFI). PATIENTS AND METHODS: This post hoc analysis of a multicenter, open-label, 1-year, Phase 3 study of extended-regimen COC with 30 µg EE/150 µg levonorgestrel (LNG) for 84 days and EE 10 µg for 7 days included 799 sexually active, adult women who completed at least one 91-day cycle of therapy. Subjects recorded bleeding and spotting episodes daily using electronic diaries. Logistic regression analyses are reported as ORs with 95% CIs. RESULTS: There was a 10% increase (OR =1.102; 95% CI: 1.006–1.206) in the likelihood of reporting no scheduled bleeding for each additional 91-day cycle completed. From the third 91-day cycle, more than one fifth of women reported no scheduled bleeding (third cycle =23% [121/533]; fourth cycle =22% [97/446]). Among women who reported no scheduled bleeding at Cycle 1 (136/758 [18%]), ≥45% showed sustained lack of scheduled bleeding in later cycles. There were increases of 53% (OR =1.531; 95% CI: 1.393–1.683) and 31% (OR =1.307; 95% CI: 1.205–1.418) in the likelihood of reporting 0 to ≤6 days vs >6 days of unscheduled bleeding and spotting, respectively, for each additional 91-day cycle. By Cycle 2, more than 80% of women reported no unscheduled bleeding or ≤6 days of unscheduled bleeding during each 91-day cycle. CONCLUSION: Improved cycle control with decreased bleeding over time was shown during extended-regimen COC with 30 µg EE/150 µg LNG for 84 days and continuous low-dose EE instead of the traditional 7-day HFI. Women considering this regimen should be informed that those who complete at least one 91-day COC cycle will likely experience less bleeding/spotting in future cycles.